A Grounded Theory Approach to Physical Activity and Advanced Cancer: A Qualitative Study Protocol. Issue 5 (30th November 2015) - Lowe, Sonya S.; Milligan, Christine; Watanabe, Sharon M.; Brearley, Sarah G.
Background: Physical activity has demonstrated benefits in cancer-related fatigue and physical functioning in early-stage cancer patients, however the role of physical activity at the end stage of cancer has not been established. To challenge positivist–empiricist assumptions, I am seeking to develop a new theoretical framework that is grounded in the advanced cancer patient's experience of activity. Aim: To gain an in-depth understanding of the experience of activity and quality of life in advanced cancer patients. Objectives: (1) To explore the meaning of activity for advanced cancer patients in the context of their day-to-day life, (2) to elicit advanced cancer patients' perceptions of activity with respect to their quality of life, and (3) to elicit advanced cancer patients' views of barriers and facilitators to activity in the context of their day-to-day life. Study Design: A two-phase, cross-sectional, qualitative study will be conducted through the postpositivist lens of subtle realism and informed by the principles of grounded theory methods. Study Methods: Advanced cancer patients will be recruited through the outpatient department of a tertiary cancer center. For Phase one, participants will wear an activPAL™ activity monitor and fill out a daily record sheet for seven days duration. For Phase two, the activity monitor output and daily record sheets will be used as qualitative probes for face-to-face, semistructured interviews. Concurrent coding, constant comparative analysis, and theoretical sampling will continue with the aim of achieving as close as possible to theoretical saturation. Ethics and Discussion: Ethical and scientific approval will be obtained by all local institutional review boards prior to study commencement. The findings will generate new mid-level theory about the experience of activity and quality of life in advanced cancer patients and aid in the development of a new theoretical framework for designing interventions for this population.